cos θ = cos ∝

How to find the general solution of an equation of the form cos θ = cos ∝?

Prove that the general solution of cos θ = cos ∝ is given by θ = 2nπ ± ∝, n ∈ Z.

Solution:

We have,

cos θ = cos ∝

⇒ cos θ - cos ∝ = 0 

⇒ 2 sin \(\frac{(θ   +  ∝)}{2}\) sin \(\frac{(θ   -  ∝)}{2}\) = 0

Therefore, either, sin \(\frac{(θ   +  ∝)}{2}\) = 0 or, sin \(\frac{(θ   -  ∝)}{2}\) = 0

Now, from sin \(\frac{(θ   +  ∝)}{2}\) = 0 we get, \(\frac{(θ   +  ∝)}{2}\) = nπ, n ∈ Z

⇒ θ = 2nπ - ∝, n ∈ Z i.e., (any even multiple of π) - ∝ …………………….(i)

And from sin \(\frac{(θ   -  ∝)}{2}\) = 0 we get,

\(\frac{(θ   -  ∝)}{2}\) = nπ, n ∈ Z                  

⇒ θ = 2nπ + ∝, m ∈ Z i.e., (any even multiple of π) + ∝ …………………….(ii)

Now combining the solutions (i) and (ii) we get,

θ = 2nπ ± ∝, where n ∈ Z.

Hence, the general solution of cos θ = cos ∝ is θ = 2nπ ± , where n ∈ Z.


Note: The equation sec θ = sec ∝ is equivalent to cos θ = cos ∝ (since, sec θ = \(\frac{1}{cos  θ}\) and sec ∝ = \(\frac{1}{cos  ∝}\)). Thus, sec θ = sec ∝ and cos θ = cos ∝ have the same general solution.

Hence, the general solution of sec θ = secs ∝ is θ = 2nπ ± , where n Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)


1. Find the general values of θ if cos θ = - \(\frac{√3}{2}\).

Solution:

cos θ = - \(\frac{√3}{2}\)

cos θ = - cos \(\frac{π}{6}\)

cos θ = cos (π - \(\frac{π}{6}\))

cos θ = cos \(\frac{5π}{6}\)

⇒ θ = 2nπ ± \(\frac{5π}{6}\), where n Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)


2. Find the general values of θ if cos θ = \(\frac{1}{2}\)

Solution:

cos θ = \(\frac{1}{2}\)

cos θ = cos \(\frac{π}{3}\)

θ = 2nπ ± \(\frac{π}{3}\), where n Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)

Therefore the general solution of cos θ = \(\frac{1}{2}\) is θ = 2nπ ± \(\frac{π}{3}\), where, n = 0, ± 1, ± 2, ± 3, ± 4 .....


3. Solve for x if 0 ≤ x ≤ \(\frac{π}{2}\) sin x + sin 5x = sin 3x

Solution:

sin x + sin 5x = sin 3x

sin 5x + sin x = sin 3x

2 sin \(\frac{5x + x}{2}\) cos \(\frac{5x + x}{2}\) = sin 3x

2 sin 3x cos 2x = sin 3x

2 sin 3x cos 2x - sin 3x = 0

sin 3x (2 cos 2x - 1) = 0

Therefore, either sin 3x = 0 or 2 cos 2x – 1 = 0

Now, from sin 3x = 0 we get,

3x = nπ   

x = \(\frac{nπ}{3}\) …………..(1)

similarly, from 2 cos 2x - 1 = 0 we get,

cos 2x = \(\frac{1}{2}\)

cos 2x = cos \(\frac{π}{3}\)

Therefore, 2x = 2nπ ± \(\frac{π}{3}\)

x = nπ ± \(\frac{π}{6}\) …………..(2)

Now, putting n = 0 in (1) we get, x = 0            

Now, putting n = 1 in (1) we get, x = \(\frac{π}{3}\)       

Now, putting n = 0 in (2) we get, x = ± \(\frac{π}{6}\)      

Therefore, the required solutions of the given equation in 0 ≤ x ≤ π/2 are:

x = 0, \(\frac{π}{3}\), \(\frac{π}{6}\).












11 and 12 Grade Math

From sin θ = -1 to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.